(untitled) (Cultura Económica, 2019)
The paper deals with the subject of distributive justice in economy, from a confronted presentation of the main ethical theories of different economists. Starting from the widely accepted concept of distributive justice, as bound to a function of the government, the author intends to demonstrate the opposite perspective, through the analysis of Nash’s method, the concept of ignorance veil developed by Harsanyi, the egalitarian ideas of Rawls and Sen, Dworkin’s responsibility concept, Roemer’s notion of equal opportunities, and finally, Nozick’s ethics in favor the voluntary distribution of resources. The aim pursued by the author is to find arguments in favor of voluntary ethics through the analysis of different models of distributive justice.